(untitled) (Actual Problems of Psychology in Educational Institutions, 2019)
The article presents the results of the analysis of the psychological and pedagogical aspects of formatting the situation of success in the educational process. The essence of the situation of success is revealed as one of the methods of organizing children’s activities. The relevance and significance of the motivation for success in the process of teaching younger schoolchildren in the NUS conditions is noted. The author emphasizes that students experience success in learning is an important resource for the child’s personal development. The author presents the results of an empirical study of the motivation for the success of schoolchildren. The conclusion is made about the need to systematically create a situation of success for younger students in the educational process.